GENDER SEKTOR PERIKANAN PADA KELOMPOK NELAYAN KARANG PUTIH DI KAWASAN MEGAMAS WENANG SELATAN KOTA MANADO - Zwensy Elizabeth Erina Lempoy; Swenekhe S. Durand; Djuwita R.R. Aling; Jardie A. Andaki; Grace O. Tambani; Olvie V. Kotambunan (Universitas Sam Ratulangi, 2023)
Abstract The aim of this research is to identify gender differences in traditional fishing businesses in the Megamas area, Wenang Village, Manado City. This research uses a survey method. This research was conducted to determine the role of gender in the fishing business of the Karang Putih fishing group. The sampling method used purposive sampling to obtain fishermen and family members involved in fishing businesses in the southern Megamas Wenang area. Descriptive techniques were used to analyze gender according to USAID (2010) guidelines, namely identifying, understanding, and describing gender differences. Gender analysis components include: 1) Data analysis separated by gender and information; and 2) Check and separate gender data and information collected through surveys. In this research, examination and separation of roles was carried out through questionnaires and interviews. Based on the results and discussion, it can be concluded: there are gender differences in the fisheries sector in the